THE CORRELATION OF OBESITY INDEX AND THE LEVEL OF TRIGLYCERIDE IN VILLAGERS - Fenty Fenty; Lucia Wiwid Wijayanti; Aris Widayati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
The obesity index is a parameter that describes general and central obesity. Obesity prevalence tends to increase in the rural areas of Indonesia. The increased prevalence of obesity is correlated with increased cardiovascular prevalence and diabetes. Dyslipidemia is also a risk factor for cardiovascular disease and is closely related to obesity. Obesity is an accumulation of excessive triglyceride levels and stored in adipose tissue that can contribute to the onset of coronary heart disease. This was an analytical observational study with a cross-sectional design. Research subjects were the rural community in Bonjoroyo village, Kulonprogo Regency, DIY which fulfilled the inclusion criteria. The data obtained were obesity index data (Body Mass Index/BMI, Waist Circle/LP, Waist Round/RLPP Ratio, Body Waist Ratio/RLPTB) and triglyceride levels which were then analyzed statistically with normality test and continued with correlation Spearman test with a 95% confidence level. The results showed that BMI, LP, and RLPTB measurements were significantly positively correlated with moderate-to-weak correlation strength in fasting blood triglyceride levels (r:0.435; p:0.000; r:0.362; p:0.002; r:0.347; p:0.004) in males. Measurements of BMI, LP, and RLPTB were positively correlated with a weak correlation strength against fasting blood triglyceride levels (r: 0.193; p: 0.028; r: 0.226; p: 0.010; r: 0.214; p: 0.014) in females. The RLPP obesity index did not show significant correlations to fasting triglyceride levels in rural communities.